Design challenges of implantable pressure monitoring system - Jiang, Guangqiang (Frontiers in Neuroscience, 2010)
Pressure in various organs and body parts, such as blood vessels, heart, brain, eyes, bladder and GI tracts, is an important indication of health. Long term, continuous pressure monitoring is critically needed for a number of applications. When combined with existing neuro-prosthetics devices, they may provide better solutions to many neural disorders. First efforts toward a long term implantable pressure-monitoring system were initiated more than forty years ago. However, a reliable, safe and implantable pressure sensor for long-term applications is not yet commercially available. This paper attempts to reveal the design challenges associated with the development of a long-term implantable pressure sensor.